The State of the Sympatho-Adrenal System and Immune Status in Patients with Coronary Heart Disease (Eurasian Medical Research Periodical, 2023)
Coronary heart disease (CHD) has acquired not only important medical, but also social significance in recent years due to an increase in morbidity, high mortality, disability of various ages and professions [1]. Recent studies indicate that in order to understand the development of coronary heart disease, further study of blood circulation regulation systems, in particular the sympathetic-adrenal system (SAS), is necessary [2,10]. A change in the activity of SAS is essential in the pathogenesis of coronary heart disease.